Quality evaluation of beef parties extended with cowpea [vigna unguiculata (L) walp] flour (2011)
The objective of this study was to evaluate the physicochemical and sensory characteristics of beef patties extended with cowpea flour (CF). Lean beef (1kg) was used for this study. The surface fats and connective tissues were trimmed off the meat which was ground and used to prepare beef filling. Cowpea flour was incorporated into the dough to form the treatments viz: Treatment 0 = (Control) 0% CF inclusion. Treatment 1 = 10% CF inclusion. Treatment 2 = 20% CF inclusion. Treatment 3 = 30% CF inclusion, Treatment 4 = 40% CF inclusion and treatment 5 =50% CF inclusion. 50g of beef filling was incorporated into each dough which was cut and folded in half to seal off the beef filling completely within the dough. The patties was brushed with fresh egg albumen and baked in clean pans greased with margarine in the oven at 180˚C between 25 and 30mins. Physicochemical and sensory attributes of the beef patties were determined. The results showed that water holding capacity and thermal shortening increased (p<0.05) as the CF inclusion level increased while cooking loss reduced (p<0.05) at 30% CF inclusion and increased (p<0.05) between 40 and 50%. Cooking weld was higher (p<0.05) at 30% CF inclusion and decreased between 40 and 50%. The chemical attributes of beef patties extended with CF as well as colour, flavour, texture and overall acceptability scores were higher (p<0.05) at 30% inclusion level. It is suggested therefore, that beef patties could be extended with CF up to 30% for optimum physicochemical attributes and consumers acceptability.